Thermodynamic constants of formation of disulfide anion in aqueous solutions. (15th May 2022) - Avetisyan, Khoren; Kamyshny, Alexey
Abstract: This study is aimed at precise measurement of thermodynamic constants of disulfide (S2 2− ) formation. It was demonstrated that these constants, K, for formation of longer polysulfides for reaction between hydrogen sulfide and orthorhombic cyclooctasulfur (α-S8 ) measured by independent techniques (potentiometry, spectrophotometry, chromatography) are in good agreement. For the most abundant polysulfides, S4 2−, S5 2− and S6 2−, the reported ranges of p K values are ≤0.72 p K units. On the other hand, p K2 values of the formation of S2 2− in this reaction measured by different techniques span from 11.46 to 14.43. The main difficulty in measurement of K2 is low abundance of disulfide in the solutions saturated with respect to α-S8 . In this work, we applied chromatographic analysis for the samples, which are highly undersaturated with respect to α-S8 . The results show that robust determination of K2 may be achieved at the molar ratio of S 0 to S(II) ≤ 0.064. At these conditions the value of p K2 at 25 °C was found to be 12.77 ± 0.08. Based on this value, the standard Gibbs free energy of S2 2− formation was calculated. The standard enthalpy of formation and molar entropy were derived from the data obtained in experiments at the temperature range of 10 °C to 70 °C. Calculations based on these thermodynamic values show that while disulfide accounts for only a minor fraction of polysulfide zero-valent sulfur at saturation with α-S8, it can become the most abundant polysulfide at low S 0 to S(II) molar ratios. In marine sediments and water columns low molar polysulfide S 0 to S(II) ratio may exist in hydrogen sulfide-rich zero valent sulfur-poor systems as well as, due to kinetic constraints, in the zero valent sulfur-rich systems. Results of our work suggest that at the molar ratio of polysulfide S 0 to S(II) > 0.064, the calculation of disulfide concentration should be based on concentrations of hydrogen sulfide and other polysulfides and the set of thermodynamic constants provided in this work. At the lower polysulfide S 0 to S(II) ratios, the disulfide concentration should be either measured directly or calculated in case that it is below the detection limit of quantification method.